(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
Professor James Young Simpson, with apologies for an article about Greek antiquities rather than Scottish ones, wrote an article to bring attention to several examples of Greek medical vases with inscriptions referring to lycium, a medicine that he found mention of in Galen and Dioscorides, among others. The professor wished to remark on the bottles because there was so little material evidence of Ancient Greek medical practices, in comparison especially with Ancient Roman medicine. The meeting minutes for March 8, 1852 are appended on, mainly a list of donations mades to the Society.